Dollarization in Cambodia : Causes and Policy Implications - Braiton, Nombulelo (IMF Working Papers; Working Paper ;, 2011)
Over the past decade, Cambodia has become Asia's most dollarized economy. In contrast, dollarization in neighboring Lao P.D.R., Mongolia, and Vietnam has been either declining or broadly stable. Somewhat paradoxically, growing dollarization in Cambodia has occurred against the backdrop of greater macroeconomic and political stability. The usual motive, currency substitution, does not appear to have been a factor. As the volume of dollars increased over the years, so has the volume of riel. A strong inward flow of dollars related to garments sector exports, tourism receipts, foreign direct investment, and aid, has benefitted the dollar based urban economy. The riel based rural economy has, however, lagged behind. Given international experience in de-dollarization, a carefully managed market based strategy, supported by a continued stable macroeconomic environment is essential for Cambodia's de-dollarization.